The maracá in the beginning of european contact: its role in tupinambá society as a religious token and musical instrument (Música Hodie, 2016)
This study draws upon three sixteenth-century primary sources that describe the first-hand impressions ofthe land and people of Brazil by European travellers. In discussing the religious and social system of the Tupinambá,this study explores the role and significance of music and of the maracá rattle for this peculiar coastal society, asdescribed and depicted by Hans Staden, André Thevet, and Jean de Léry. Although these travel accounts differ instyle, approach, and empiric context, they frequently intersect and complement one another, thus helping modernapproaches to reconstruct some of the musical idiosyncrasies pertaining to Tupinambá ritual practices. Finally, inanalyzing the narrative and iconography in these sources, this study searches for a place for music and the maracáwithin this complex social system, thus aiming to shed light on its purpose and usage at the time.Keywords: Maracá; Tupinambá; Ritual music; Travel account; 16th century.